Analysis of alternative configurations of heat recovery process in small and medium scale combined cycle power plants. (15th November 2017) - Kalina, Jacek
Highlights: Alternative configuration of HRSG is proposed. Bottoming of combined cycle power plant with ORC is considered. Application of efficient gas turbines with low exhaust gas temperature is taken into account. Energy and exergy efficiencies of heat recovery process are presented. Computer simulations reveal possibilities for performance improvement. Abstract: In the paper various configurations of the heat recovery process in combined gas and steam cycle power plants of complex structures are examined. Proposed modifications concern mainly hot side temperature profile. It has been assumed that two gas turbines will be installed in the system with a common single pressure heat recovery steam generator. Exhaust gas from the boiler is introduced into the low-temperature Rankine cycle with an organic working fluid. Two configurations of heat exchangers have been proposed, that can be considered as an alternative solution to the conventional structures currently in use. Energy and exergy efficiency values have been calculated for different parameters of steam. In addition, the temperature of exhaust gas from gas turbines was assumed to be different, which corresponds to the use of turbines of different efficiency classes. It has been shown that, with appropriately high steam parameters and appropriately selected gas turbines, the proposed alternatives lead to an improvement of the system performance.